Analysis of the EAR conversion method for air pollutant emission concentration. (December 2020) - Ye, Yalan; Wang, Hongming; Jiang, Wenhao
Abstract: In the control of air pollutant emissions, the measured emission concentration should be converted into the standard condition. The converted concentration is obtained in order to determine whether the emissions meet requirements. At present, there are several conversion methods available, and the EAR (excess air ratio) conversion method is one of them. Based on the conversion mechanism of air pollutant concentration, the origin of EAR conversion method was deduced and analyzed in this paper. The results show that the EAR method is a simplified method that is only suitable for the fuels with fuel composition factor close to zero, such as coal, biofuel, solid waste, oil, etc. It is not suitable for the fuels with big fuel composition factor, such as blast furnace gas, converter gas and producer gas, etc.